Relationship Between Age, Parity Status With The Incidence Of Postpartum - Sri Yunita Suraida Salat; Emdat Suprayitno (Healthy-Mu Journal, 2022)
Every woman always looks forward to when she can take care of the baby she has been carrying for nine months. However, sometimes this period becomes unpleasant and can even make mothers depressed, which we often know as the baby blues or postpartum blues. This study aimed to determine whether there was a relationship between age and postpartum mother status with the incidence of postpartum blues in Marengan Laok Village. This research is an analytic study with a cross-sectional approach. The research variables were age, parity status, and the incidence of postpartum blues. The research sample was postpartum mothers in June-August 2021 in Marengan Laok Village, as many as 13 mothers with a sampling technique, namely total sampling. Data analize used Spearman rank test. The results showed that 62% of postpartum mothers were 20-30 years old, 69% of mothers had primiparous status, and 77% of postpartum mothers experienced postpartum blues. The statistical data shows a value = of 0.003 and a value = 0.001 for parity status, which means that there is a solid relationship between age and parity status with the incidence of postpartum blues in Marengan Laok village. Therefore, careful preparation is needed when a mother is planning her pregnancy